Studi Ergonomi Pada Penyiapan Lahan Sawah Lebak Menggunakan Alat Tradisional Tajak di Kabupaten Banjar Kalimantan Selatan - Indya Dewi; M. Faiz Syuaib; Tineke Mandang (PERTETA, 2011)
Abstract Traditional local farmers in South Kalimantan conventionally do the field preparation by using a traditional tool named “tajak”. This typical traditional tool is very appropriate for land preparation in marshland field which is enabling to cultivate without raising the pirit (FeS2) layer. However, it is quite difficult, hard and dangerous to operate tajak, and it’s difficult to learn by a novis operator as well. Therefore, ergonomics study will be beneficial to develop more convenient, safe and effective tajak. The result of workload analysis revealed that tajak operation is an “extremey hard” workload, whichs the avarage of IRHR is 2.14. The workload level of tajak operation is indicatively by workload intencity and swing elevation. Regarding the Total energy cost per weight (TEC’) and hours of work (JOK), the tajak operation consumes 5.36 kcal/kg.hour and need 61.07 hour/ha in average. Anthropometri and motion study analysed revealed that the dimentional suitability of tajak tool is strongly related to shoulders and waist heightly, arms length, and hands grips diameter. Based on the result of tajak anthropometri and motion analyses, for better design of tajak’s handle was recommended 75.70 cm. Keywords: tajak, marshland field, ergonomic, work load, motion analysis, anthropometri Abstrak